2022
DOI: 10.1111/jnu.12790
|View full text |Cite
|
Sign up to set email alerts
|

Impact of emotional intelligence on work performance: The mediating role of occupational stress among nurses

Abstract: Introduction An occupational stress was reported as an inhibitor of optimal performance among nurses. Emotional intelligence (EI) has emerged as a successful behavioral buffer against occupational stress and as a facilitator for better performance. This study aimed to investigate the potential relationship between nurses' EI and their work performance; and to examine the mediating role of occupational stress. Design A predictive correlational design was adopted. Method Self‐reported questionnaires were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 89 publications
1
4
0
Order By: Relevance
“…Another study found the same results of the current study by linking the emotional intelligence with job performance of nurses [8]. A study was conducted in Saudi Arabia by Alsufyani et al [33] to examine the relationship between EI and work performance among nurses and found that emotional intelligence and work performance are positively associated. Nurses with a high level of emotional intelligence are capable to handle work which results in better overall work performance [14].…”
Section: Discussionsupporting
confidence: 84%
“…Another study found the same results of the current study by linking the emotional intelligence with job performance of nurses [8]. A study was conducted in Saudi Arabia by Alsufyani et al [33] to examine the relationship between EI and work performance among nurses and found that emotional intelligence and work performance are positively associated. Nurses with a high level of emotional intelligence are capable to handle work which results in better overall work performance [14].…”
Section: Discussionsupporting
confidence: 84%
“…Although there is a dearth of literature regarding the relation between emotional intelligence and quiet quitting, evidence suggests a positive impact of emotional intelligence on several work-related variables. In particular, several studies showed that emotional intelligence had a positive effect on work performance [27] [31] , job satisfaction [9] , [26] , [27] , organizational commitment [44] , and clinical competence [45] among nurses. Since nurses are usually exposed to high levels of responsibility, stress, and emotional demands, emotional intelligence is a crucial tool to achieve the most beneficial outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the relationship between emotional intelligence and work-related variables among nurses. In particular, high emotional intelligence has been linked to higher job satisfaction [9] , [26] , [27] , higher work performance [27] [31] , higher professional success [32] , less job burnout [9] , [33] , less occupational stress [31] , and lower turnover intentions [34] , [35] . In other words, high emotional intelligence is associated with the most beneficial work-related outcomes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…EI was measured as the sum of the scores for all 33 items, with a score range of 33–165, where a score between 33 and 77 suggests a low EI level, a score between 78 and 121 indicates a moderate level and a score between 122 and 165 denotes a high level of EI (Schutte et al, 1998 ). The SSEIT is a validated measure that is widely used for assessing EI, with a Cronbach’s alpha ranging from 0.80 to 0.94 (Abou Hashish & Bajbeir, 2018 ; Aldossary et al, 2019 ; Alsufyani et al, 2022 ; Schutte et al, 2007 ). The present research assessed the questionnaire’s reliability by calculating Cronbach’s alpha, yielding a value of 0.93, which was considered to be within normal values.…”
Section: Methodsmentioning
confidence: 99%